The Relationship of Work Reward to Supporting Factors for the Productivity of Honey Workers - Linda, Nur; susilawati, Susilawati; Hasibuan, Rapotan (GLOBAL HEALTH SCIENCE GROUP, 2024)
Rewards are given to encourage someone to act more actively to increase or improve their performance. Rewards are the most important management tool to achieve the desired goals of a business. The International Labor Organization Statistics (ILOSTAT) releases data on labor productivity in Indonesia with growth rates, namely in 2014 (3.31%), 2015 (4.10%), 2016 (3.71%), 2017 (1, 97%), in 2018 (3.05%), and in 2019 (93.68%). From this data, progress in labor productivity in Indonesia tends to be low in percentage and fluctuates every year. In Takoma itself, the performance of workers is hampered by weather and seasonal factors. Therefore, workers are not productive at work. The success of a business is closely related to the quality of the human resources it has, because human resources have an important role as actors, movers and determinants of organizational work results based on the company's operational activities, both in quality and quantity. In this case, social disparities often occur within the organization which results in a lack of effectiveness in the performance of workers. Basically, companies expect capable human resources, but the most important thing is the desire to work hard and achieve optimal work results. On the island of Sumatra, one of the honeys that can be found is honey in Takoma, which is located in Pamatang Sidamanik District, Simalungun Regency, North Sumatra Province. The Pamatang Sidamanik area is the best place to produce tea, coffee and honey. Takoma is an abbreviation of Taro, Coffee, Honey which is made in Sait Buttu Saribu Village. The aim of this research is to determine the role of rewards in increasing the productivity of honey workers in Sait Buttu Saribu Village. This research uses a quantitative methodology with a cross sectional design. The population in this study were honey workers in Sait Buttu Saribu Village, totaling 16 respondents. From the total population obtained, the sample that the researcher took was the total of that population, because the researcher used a total sampling technique. Primary data collected directly by researchers through questionnaires from previous research. The results of the bivariate statistical test using Chi Square show that the average p-value is 0.000 (<0.05), meaning that there is a significant relationship between the reward variable and the worker productivity variable. It is hoped that business owners will pay attention and provide more rewards to increase worker productivity.